2022
DOI: 10.3390/nu14214600
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Counteracts the Hypoxic-Induced Inflammatory and Metabolic Alterations in 3T3-L1 Adipocytes

Abstract: Background: Hypoxia is caused by the excessive expansion of the white adipose tissue (AT) and is associated with obesity-related conditions such as insulin resistance, inflammation, and oxidative stress. Docosahexaenoic acid (DHA) is an omega-3 fatty acid reported to have beneficial health effects. However, the effects of DHA in AT against hypoxia-induced immune-metabolic perturbations in adipocytes exposed to low O2 tension are not well known. Consequently, this study aimed to evaluate the impact of DHA on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Intriguingly, after early intervention with RRTP, MDA and MPO decreased significantly, while SOD and GSH increased significantly. The RRTP-regulated lipid and amino acid differential metabolites, including docosahexaenoic acid ( Tatsumi et al, 2022 ; Younes et al, 2022 ), docosapentaenoic acid ( Wang et al, 2019 ) and histidine ( Thalacker-Mercer and Gheller, 2020 ), identified in our metabolomics study, have effects on reducing inflammation and alleviating oxidative stress. Furthermore, Bacteroidota is one of the most aerobically tolerant anaerobic bacteria, and its relative abundance increases significantly under ascending levels of oxidative stress in the organism ( Zafar and Saier, 2021 ).…”
Section: Resultsmentioning
confidence: 95%
“…Intriguingly, after early intervention with RRTP, MDA and MPO decreased significantly, while SOD and GSH increased significantly. The RRTP-regulated lipid and amino acid differential metabolites, including docosahexaenoic acid ( Tatsumi et al, 2022 ; Younes et al, 2022 ), docosapentaenoic acid ( Wang et al, 2019 ) and histidine ( Thalacker-Mercer and Gheller, 2020 ), identified in our metabolomics study, have effects on reducing inflammation and alleviating oxidative stress. Furthermore, Bacteroidota is one of the most aerobically tolerant anaerobic bacteria, and its relative abundance increases significantly under ascending levels of oxidative stress in the organism ( Zafar and Saier, 2021 ).…”
Section: Resultsmentioning
confidence: 95%
“…[ 4 ] Docosahexaenoic acid (DHA) can exert potential anti-obesity effects by reducing the secretion of inflammatory adipokines, oxidative stress, lipolysis, and apoptosis. [ 5 ] N-arachidonoyl dopamine (N-ADA) possesses anti-inflammatory properties. [ 6 ] Our results showed that, compared to the control group, the MMCS and MSCS groups had higher levels of IL-6 and 3-HA and lower levels of N-ADA.…”
mentioning
confidence: 99%